When Rubrics Collide: One Undergraduate Writing Tutor's Experience Negotiating Faculty and Institutional Assessments - Kelli Martin, BA (Park University, 2013)
This article recounts one undergraduate writing tutor's experience helping a fellow peer navigate an institutional assessment rubric that seemed to contrast the assessment criteria provided by the student's instructor. This article presents a reflection on that experience, framed by Hutchings, Huber, and Ciccone's (2011) work on institutional assessment and the scholarship of teaching and learning.